2015
DOI: 10.1371/journal.pone.0127524
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Metabolizing Activity, Protein and Gene Expression of UDP-Glucuronosyltransferases Are Significantly Altered in Hepatocellular Carcinoma Patients

Abstract: UDP-glucuronosyltransferases (UGTs), the most important enzymes in body detoxification and homeostasis maintaining, govern the glucuronidation reaction of various endogenous and environmental carcinogens. The metabolic function of UGTs can be severely influenced by hepatocellular carcinoma (HCC), the fifth prevalent and third malignant cancer worldwide. Particularly in China, HBV-positive HCC account for approximately 80% of HCC patients. But rare papers addressed the alteration on the metabolism of UGTs speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…3C). We also show UGT2B7 downregulation in HCC, a finding that was recently reported by others (Lu et al, 2015;Yan et al, 2015a). Previous studies have also reported downregulation of three other UGTs (1A1, 1A4, and 1A9) in HCC (Lu et al, 2015;Yan et al, 2015a).…”
Section: Phase I Enzymesupporting
confidence: 90%
“…3C). We also show UGT2B7 downregulation in HCC, a finding that was recently reported by others (Lu et al, 2015;Yan et al, 2015a). Previous studies have also reported downregulation of three other UGTs (1A1, 1A4, and 1A9) in HCC (Lu et al, 2015;Yan et al, 2015a).…”
Section: Phase I Enzymesupporting
confidence: 90%
“…The measured UGT2B7 activity in ALF rats was only approximately 70% of that in the control rats, in agreement with the decrease in protein expression of hepatic UGT2B7. These results were consistent with the findings in patients with liver disease [49,50] . The intestinal metabolism of AZT was also taken into consideration because UGT2B7 is also expressed in the intestine [51] , but the formation of GAZT in intestinal microsomes was not detected.…”
Section: Discussionsupporting
confidence: 93%
“…Few previous studies have investigated UGT3A1 variants in NSCLC. However, a recent study found that the UGT3A gene family catalyze biotransformation of endogenous and environmental carcinogens including drugs (Lu et al, 2015 ). Additionally, UGT3A1 differentiated primate species by participation in sugar conjugation during metabolism and elimination of lipophilic metabolites and exogenous chemicals (Meech and Mackenzie, 2010 ).…”
Section: Discussionmentioning
confidence: 99%